Evaluasi Tes Kemampuan Bahasa Arab di UIN Syarif Hidayatullah Jakarta: Analisis Kesesuaian dengan Standar CEFR dan ACTL - Ainur Rasidah,; Khaerul Umam,; Fatmah Zaenal Arifin Hambali,; Ubaid Ridho,; Raswan, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the system and implementation of the Test of Arabic as a Foreign Language (TOAFL) at UIN Syarif Hidayatullah Jakarta, and assess its compliance with the international standards of the Common European Framework of Reference for Languages ​​(CEFR) and the American Council on the Teaching of Foreign Languages ​​(ACTFL). The results show that the TOAFL system has a well-established institutional structure and administrative mechanism, but conceptually it is still oriented towards the language knowledge testing paradigm and does not yet measure communicative competence as required by the CEFR and ACTFL. In terms of content, TOAFL test items are dominated by linguistic aspects (grammar and vocabulary), with a very limited portion of pragmatic and socio-cultural abilities. Therefore, TOAFL results cannot be directly converted to CEFR competency levels (A1–C2) or ACTFL categories (Novice–Superior). This study recommends developing an alignment framework between TOAFL and international standards through the development of performative indicators, strengthening oral and written test rubrics, and providing assessment literacy training for Arabic language teachers. These findings are expected to strengthen the competitiveness of Indonesia's Arabic language assessment system in the context of the globalization of Islamic higher education.